PENGARUH EKUITAS MEREK DAN BAURAN PROMOSI TERHADAP MINAT BELI PRODUK MITSUBISHI (Studi pada PT.Nusantara Berlian Motor Pekanbaru) - Novika Pakpak; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of brand equity and promotional mix on consumer buying interest at PT. Nusantara Berlian Motor Pekanbaru partially and simultaneously. This study uses a questionnaire as a data collection tool that is distributed to 100 consumers of PT. Nusantara Berlian Motor Pekanbaru. Data from the questionnaire was further processed using descriptive analysis and statistical analysis using SPSS 25.0 by conducting validity, reliability testing, simple linear regression analysis, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing consisting of t-test (partial) and test F (simultaneous). The results of this study indicate that the results of the first hypothesis testing that is brand equity on consumer buying interest show t arithmetic (6.949)> t table (1.984), meaning that brand equity has a significant effect on consumer buying interest. The results of the second hypothesis testing that is the promotional mix on consumer buying interest show t arithmetic (10.861)> t table (1.984), meaning that the promotional mix has a significant effect on consumer buying interest. The results of testing the third hypothesis, namely brand equity and promotion mix on consumer buying interest show F arithmetic (59.993)> F table (3.09), meaning that brand equity and promotional mix have a significant effect on consumer buying interest. Keywords: Brand Equity, Promotion Mix, Consumer Purchase Interest